2017
DOI: 10.1111/aos.13617
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in retinal vascular parameters associated with successful panretinal photocoagulation in proliferative diabetic retinopathy: A prospective clinical interventional study

Abstract: PurposeWe aimed to investigate changes in retinal vascular geometry over time after panretinal photocoagulation (PRP) in patients with proliferative diabetic retinopathy (PDR).MethodsThirty‐seven eyes with PDR were included. Wide‐field fluorescein angiography (Optomap, Optos PLC., Dunfermline, Scotland, UK) was used to diagnose PDR at baseline and to assess activity at follow‐up month three and six. At each time‐point, a trained grader measured retinal vessel geometry on optic disc (OD) centred images using se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Earlier studies have found a decrease in fractal dimension in patients with PDR, who underwent PRP 35 . Torp TL et al 36 found an increase in the arteriolar vessel caliber, which could represent a positive response to the PRP treatment, with a lower hypoxic load on the retina and a subsequent autoregulatory arteriolar dilation. The present study demonstrates that an increase in the parafoveal PD 6 months after PRP, can independently predict the progression of PDR, and might be a potential non-invasive OCTA marker of DR activity.…”
Section: Discussionmentioning
confidence: 96%
“…Earlier studies have found a decrease in fractal dimension in patients with PDR, who underwent PRP 35 . Torp TL et al 36 found an increase in the arteriolar vessel caliber, which could represent a positive response to the PRP treatment, with a lower hypoxic load on the retina and a subsequent autoregulatory arteriolar dilation. The present study demonstrates that an increase in the parafoveal PD 6 months after PRP, can independently predict the progression of PDR, and might be a potential non-invasive OCTA marker of DR activity.…”
Section: Discussionmentioning
confidence: 96%
“… 18 27 In an earlier prospective study, performed at our unit, we found no difference in F D at baseline between patients with progression and non-progression at follow-up month six. 32 This difference could be due to the usage of two different computer softwares, the SIVA and VAMPIRE softwares. There are some evident differences between the two softwares.…”
Section: Discussionmentioning
confidence: 99%
“…[27] Higher tortuosity is thought to be a marker of tissue hypoxia and vascular endothelial growth factor (VEGF) production. [55, 56] Torp et al [57] demonstrated a decrease in peripapillary vessel tortuosity 6 months following successful PRP (defined as no further development of neovascularization or decline in visual acuity compared to baseline). We propose that the significant decrease in perifoveal tortuosity one year following successful PRP in the current study is in line with improved macular perfusion on OCTA [27], which would explain the decline in vessel tortuosity.…”
Section: Discussionmentioning
confidence: 99%